Spillover effects of increased health insurance enrollment on workers' compensation insurance. Issue 1 (16th March 2020) - Baggett, Courtney B.; Cole, Cassandra R.; Crowley, George; Sirmans, E. Tice
Abstract: The Patient Protection and Affordable Care Act (ACA) was designed to increase the accessibility and affordability of health insurance. While the ACA did not contain direct provisions related to workers' compensation (WC), because health‐related coverage is a significant portion of WC costs, the ACA could have unintentionally impacted the WC market. Specifically, expanded health insurance enrollment could reduce WC losses and result in higher performance among insurers participating in the WC market. Using insurer‐state level data, we consider the impact of increased health insurance enrollment on the performance of property‐casualty (PC) insurers. Utilizing multiple measures of performance, we find that the post‐ACA period is generally associated with greater profitability for PC insurers operating in the WC market, a positive unintended consequence of this federal regulation.